Biodiversity conservation in human-modified Amazonian forest landscapes - Peres, Carlos A.; Gardner, Toby A.; Barlow, Jos; Zuanon, Jansen; Michalski, Fernanda [UNESP]; Lees, Alexander C.; Vieira, Ima C. G.; Moreira, Fatima M. S.; Feeley, Kenneth J. (Elsevier B.V., 2010)
Amazonia (sensu lato) is by far the largest tropical forest region, but has succumbed to the highest absolute rates of tropical deforestation and forest degradation, driven by rapid frontier expansion, road-building, and spontaneous or government-subsidized migration. The large area-through-time and paleo-climatic stability of Amazonian forests may help explain the high regional to local scale plant and animal species diversity of true forest specialists and high ecological sensitivity to contemporary land-use change. We describe the prevailing forms of anthropogenic disturbance that affect forest organisms in the context of the geographic and evolutionary background that has shaped the degree to which forest species may be resilient to environmental change. The fate of Amazonian biodiversity will partly depend upon the interaction between land-use and climate change, and the extent to which seasonally-dry forests can retain immunity against catastrophic recurrent wildfires. This review illustrates the importance of considering interactions between different forms of forest disturbance to develop effective conservation policy. We conclude with some considerations of the policy agenda necessary to protect forest cover and forest biodiversity at a meaningful scale across the Amazonian biome. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Amazonia; Andes; Biodiversity; Deforestation; Forest disturbance; Human-dominated landscapes; Land use